2018
DOI: 10.1007/s12033-018-0082-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Engineering of Glycyrrhizin Pathway by Over-Expression of Beta-amyrin 11-Oxidase in Transgenic Roots of Glycyrrhiza glabra

Abstract: Glycyrrhiza glabra is one of the most important and well-known medicinal plants which produces various triterpene saponins such as glycyrrhizin. Beta-amyrin 11-oxidase (CYP88D6) plays a key role in engineering pathway of glycyrrhizin production and converts an intermediated beta-amyrin compound to glycyrrhizin. In this study, pBI121:CYP88D6 construct was transferred to G. glabra using Agrobacterium rhizogene ATCC 15834. The quantitation of transgene was measured in putative transgenic hairy roots using qRT-PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…These data showed the great impact of these two genes on the glycyrrhizin biosynthetic pathway. In the case of a research on metabolic engineering of glycyrrhizin biosynthetic pathways including SQS1 and CYP88D6, an increased amount of glycyrrhizin was observed in hairy root cultures of Glycyrrhiza plants that confirmed the results of this study (Lu et al 2008;Shirazi et al 2018). Production pattern of glycyrrhizin was more similar to the expression pattern of SQS1 gene so that the stepwise regression analysis also confirmed that 92% of the change in glycyrrhizin content is associated with SQS1.…”
Section: Effect Of Salt Stress On Glycyrrhizin Content In Rootssupporting
confidence: 84%
“…These data showed the great impact of these two genes on the glycyrrhizin biosynthetic pathway. In the case of a research on metabolic engineering of glycyrrhizin biosynthetic pathways including SQS1 and CYP88D6, an increased amount of glycyrrhizin was observed in hairy root cultures of Glycyrrhiza plants that confirmed the results of this study (Lu et al 2008;Shirazi et al 2018). Production pattern of glycyrrhizin was more similar to the expression pattern of SQS1 gene so that the stepwise regression analysis also confirmed that 92% of the change in glycyrrhizin content is associated with SQS1.…”
Section: Effect Of Salt Stress On Glycyrrhizin Content In Rootssupporting
confidence: 84%
“…GA shows a wide range of effects such as antibacterial, hepatoprotective, antiproliferative, antiallergic, and antiviral [98].…”
Section: Glycyrrhizin (Ga)mentioning
confidence: 99%
“…This molecule inhibits the chemotactic and pathogenic functions of HMGB1 by binding directly the A and B boxes [ 97 ]. GA shows a wide range of effects such as antibacterial, hepatoprotective, antiproliferative, antiallergic, and antiviral [ 98 ].…”
Section: Future Therapeutic Approachesmentioning
confidence: 99%
“…Considering these, the aim of this research was to study the metabolic pathway and biosynthetic genes functioning in diosgenin formation. The results could be applied to engineer the metabolic flux toward diosgenin biosynthesis in order to improve the accumulation of diosgenin in either the whole plant or the hairy root cultures of fenugreek, which have been considered as promising alternative platforms as compared to the wild plant . In the present study, the full‐length CDS of 14 genes involved in the diosgenin biosynthesis pathway were identified (Figures S5B–S15C).…”
Section: Discussionmentioning
confidence: 99%